Regular en el COIP, cuando en sentencia se debe imponer la prohibición de salir del domicilio o lugar determinado - Borja Borja, Byron Augusto (2016)
The current doctrinal trend is the criminal law of minimum intervention and ultima ratio which seeks to replace imprisonment or imprisonment for alternatives mediated, because the prison sentences currently in crisis by the historic failure, inadequacy and effectiveness of these penalties for effective rehabilitation and early reintegration into society ruled. In practice it is easy to see that prisons do not rehabilitate, not educate, and prepare the individual for social reintegration, in reality has become real schools of crime. The prison simply means the person uproot their natural habitat and introduce not just one cell, but in a community hostile, violent, away from the family unit and their affections. On the other hand, prison is not only detrimental to the persons deprived of freedom, but also for the family. The main effects of the harmfulness of imprisonment apply short-term primary or least dangerous criminals is the loss of economic, employment and family stability; and physical impairments, damage to health and psychological disorders in the deprived of liberty and their families. Against the background exposure and conviction about the harmfulness of compliance with the deprivation of liberty in the prisons he led to the United Nations (UN) to adopt as of December 14, 1990, the Standard Minimum Rules on the Means not custodial, also called Tokyo Rules; and in the Organization of American States (OAS), the IACHR through Resolution dated 14 March 2008, it established the Principles and Best Practices on the Protection of Persons Deprived of Liberty in the Americas. Legal instruments which are intended to promote the imposition of alternative measures prior to the offender meets certain requirements established by law. In Latin American countries, offenses punishable by short sentences a range of alternatives to imprisonment is applied, so that they do not have as strong negative impact on the individual and the people who depend on it, such as suspension of the trial to test partial confinement, prison or house arrest, fine reparations, among others. In Ecuador, only three prisons meet certain standards of rehabilitation, specifically those built in Azuay, Cotopaxi and Guayas, while other places of deprivation of liberty almost nothing has changed from the old prison system. In addition to this date there is no Suitable for older persons in the country Centre, which forces judges to provide for the enforcement of custodial sentences in public jails or in unsuitable places, which violates the constitutional rights of these people who under the Constitution require priority attention. The Constitution of the Republic of Ecuador in Article 77 paragraph 11 provides for the application of alternative sanctions to imprisonment according to the cases, terms, conditions and requirements of the Act; in Art. 60 paragraph 7 and Art. 66 of the Code Integral Criminal Assemblyman established as imprisonment the ban on leaving the residence or place determined by judgment, however, the legal body cited above, if but provides this alternative sanction, but does not indicate in which cases and what the requirements for the implementation of this alternative measure in favor of people are sentenced. The lack of regulation on the implementation of the sentence does not imprisonment of prohibition to leave the home or place specified in the judgment results in: A. Legal uncertainty because the COIP not establish legal rules clearly and accurately establish cases, terms, conditions and requirements that enable the competent authorities to impose a sanction or alternative measure; B. Violation of the constitutional right of individuals and groups of priority attention, including the right to health, decent life, to work and the best interests of the child; Lost c.- economic, employment and family or primary minimum dangerous offender stability; and d.- damage and psychological disorders in the primary offender and his family. Hence my proposal for legal reform aims to regulate the Comprehensive Organic Penal Code, the prohibition to leave the home or place specified in sentence as an alternative measure for people who require priority attention, somehow avoid the consequences indicated in the above; flexible criminal sanction regarding the place and time in which they must serve the sentence; and ensure effective rehabilitation and social reintegration. Commensurate with the social comprehensive reform of the country and made new trends in criminal policy, which translates into replace sentences of imprisonment in prisons has been made necessary by the criminal justice system and social rehabilitation of Ecuador, keeping for over a century by no deprivation of liberty or serving the sentence on the offender's home or some place other than prison, work for the community, attend mandatory prevention programs, therapies with different specialists Among other measures and alternative sanctions. To thereby harmonize the legal framework of the country with international standards and modern penal doctrine